Emerging Technology Applications to Promote Physical Activity and Health - Lee, Jung Eun (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
As technology becomes an ever-more prevalent part of everyday life, and population-based physical activity programs seek new ways to increase life-long engagement with physical activity, these two ideas have become increasingly linked. This Special Issue attempts to offer a thorough and critical examination of emerging technologies in physical activity and health promotion, considering technological interventions in different contexts (communities, clinics, schools, homes, etc.) among various populations, exploring the challenges of integrating technology into physical activity promotion, and offering solutions for its implementation. This Special Issue aims to take a broadly positive stance toward interactive technology initiatives and, while discussing some negative implications of an increased use of technology, offers practical recommendations for promoting physical activity through various emerging technologies, including, but not limited to: Active video games (exergaming); social media; mobile device apps; health wearables; mobile games, augmented reality games, global positioning and geographic information systems; and virtual reality. Offering a logical and clear critique of emerging technologies in physical activity and health promotion, this Special Issue will provide useful suggestions and practical implications for researchers, practitioners, and educators in the fields of public health, kinesiology, physical activity and health, and healthcare.